2005
DOI: 10.1079/ber2004344
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmentally induced changes in the bark of young conifers on feeding behaviour and reproductive development of adult Hylobius abietis (Coleoptera: Curculionidae)

Abstract: Young plants of Sitka spruce, Scots and Corsican pine were subject to high and low light, and high and low nitrogen treatments in a polyhouse experiment. The effect of treatments on resin duct size and nitrogen concentration in stem bark was determined together with feeding by Hylobius abietis Linnaeus on the stems of 'intact' plants and on 'detached' stems cut from the plant. Resin duct size was largest on Corsican pine and smallest on Sitka spruce and inherent variation in duct size between the three conifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In linear regressions of the relationship between the number of resin ducts and stem diameter, duct area and stem diameter, and between resin mass and duct area, a common slope was Wtted to the data where appropriate. The analysis of bio-assay data was based on an L n transformed ratio of deep/shallow feeding (L n ratio) (Wainhouse et al 2005). Prior to analysis, seven observations of zero shallow feeding were given the value of 0.05 (minimum observed value = 0.06), and one observation with zero deep feeding was given the value of 1 (minimum observed value = 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In linear regressions of the relationship between the number of resin ducts and stem diameter, duct area and stem diameter, and between resin mass and duct area, a common slope was Wtted to the data where appropriate. The analysis of bio-assay data was based on an L n transformed ratio of deep/shallow feeding (L n ratio) (Wainhouse et al 2005). Prior to analysis, seven observations of zero shallow feeding were given the value of 0.05 (minimum observed value = 0.06), and one observation with zero deep feeding was given the value of 1 (minimum observed value = 3).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of bark eaten by each weevil was measured as described by Wainhouse et al (2005). BrieXy, the stem section containing feeding damage was removed from the tree and immersed in pentane for 5 or 10 min to remove exuded resin at the feeding sites.…”
Section: Bio-assays and The Expression Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Large seedlings are generally more tolerant to pine weevil feeding because of their lower likelihood of being girdled (Selander 1993;Örlander and Nilsson 1999;Thorsén et al 2001). Moreover, the size of resin ducts, which contribute to weevil resistance in young conifers, is correlated to bark thickness and stem base diameter (Wainhouse et al 2005). For high survival rates of seedlings in areas infested with pine weevils, threshold root collar diameters of 8-9 mm for Norway spruce and 12 mm for Scots pine have been suggested (Thorsén et al 2001;Wallertz et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, insect defoliators such as the pine sawflies Neodiprion swanei and Neodiprion sertifer (Larsson and Tenow, 1984;Smirnoff and Bernier, 1973), or the poplar chrysomelids Chrysomela tremulae and Phratora vitellinae (Gruppe et al, 1999) are adversely affected by nitrogen fertilization of trees. Similarly, it has been observed that the number and size of resin ducts increases in fertilised conifers (Kytö, 1999;Wainhouse et al, 2005). Because resin compounds are toxic for bark feeders such as bark beetle and weevils or repellent for mammal herbivores such as voles and hares (Harju and Tahvanainen, 1997), it follows that fertilised trees would be less damaged by these agents.…”
Section: Site Preparationmentioning
confidence: 99%